2018
DOI: 10.1590/2177-6709.23.3.080-093.sar
|View full text |Cite
|
Sign up to set email alerts
|

Digital platform for planning facial asymmetry orthodontic-surgical treatment preparation

Abstract: Dentofacial deformities usually are surgically treated, and 3D virtual planning has been used to favor accurate outcomes. Cases reported in the present article show that orthognathic surgery carried out to correct facial asymmetries does not comprise only one treatment protocol. 3D virtual planning might be used for surgical planning, but it should also be used to diagnose the deformity, thus allowing for an analysis of the best-recommended possibilities for the orthodontic preparation that suits each individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…Es de importancia mencionar el peso clínico que va adquiriendo la planeación virtual de cirugías ortognáticas, ya que permite conocer, evaluar y analizar las ventajas de elección de cierta maniobra quirúrgica, sus posibles complicaciones e incluso medir con precisión el tejido duro y los cambios dinámicos en el tejido blando, todo en una plataforma 3D, brindando de esta forma alternativas de tratamiento para la asimetría facial, donde se decidirá si empezar con un tratamiento ortodóntico y su secuencia clínica clásica, o dar paso al abordaje quirúrgico como primera instancia. [15][16][17][18][19][20] Choi JW y colaboradores al realizar un seguimiento retrospectivo a 59 pacientes con asimetría facial vertical y horizontal, de los cuales 33 fueron sometidos a corrección quirúrgica en primera instancia y 26 recibieron primero tratamiento ortodóntico seguido de quirúrgico, al comparar a los grupos a largo plazo se determinó que en ninguno de los grupos fue necesario realizar cirugías adicionales, ya que no hubo inestabilidad oclusal o complicaciones, mostrando resultados quirúrgicos similares tanto en la asimetría vertical y horizontal, independientemente de que se haya realizado primero la cirugía o primero el tratamiento ortodóntico. Sin embargo, el tratamiento ortodóntico fue más corto en el grupo en el que se realizó primero la cirugía en comparación con el grupo en el que se realizó primero la ortodoncia.…”
Section: Discussionunclassified
“…Es de importancia mencionar el peso clínico que va adquiriendo la planeación virtual de cirugías ortognáticas, ya que permite conocer, evaluar y analizar las ventajas de elección de cierta maniobra quirúrgica, sus posibles complicaciones e incluso medir con precisión el tejido duro y los cambios dinámicos en el tejido blando, todo en una plataforma 3D, brindando de esta forma alternativas de tratamiento para la asimetría facial, donde se decidirá si empezar con un tratamiento ortodóntico y su secuencia clínica clásica, o dar paso al abordaje quirúrgico como primera instancia. [15][16][17][18][19][20] Choi JW y colaboradores al realizar un seguimiento retrospectivo a 59 pacientes con asimetría facial vertical y horizontal, de los cuales 33 fueron sometidos a corrección quirúrgica en primera instancia y 26 recibieron primero tratamiento ortodóntico seguido de quirúrgico, al comparar a los grupos a largo plazo se determinó que en ninguno de los grupos fue necesario realizar cirugías adicionales, ya que no hubo inestabilidad oclusal o complicaciones, mostrando resultados quirúrgicos similares tanto en la asimetría vertical y horizontal, independientemente de que se haya realizado primero la cirugía o primero el tratamiento ortodóntico. Sin embargo, el tratamiento ortodóntico fue más corto en el grupo en el que se realizó primero la cirugía en comparación con el grupo en el que se realizó primero la ortodoncia.…”
Section: Discussionunclassified
“…, 10 This new alternative has become an important tool to plan facial asymmetry treatments, and the 3D platform is normally used at a further preparatory step, which aims to have surgical movements planned. It allows for greater accuracy in asymmetrical patient’s treatment, from both surgical and orthodontic perspectives 11 . Some authors have reported that virtual planning increases the effectiveness as orthognathic surgery, with more accurate osteotomies than with the classic planning 12 …”
Section: Discussionmentioning
confidence: 99%
“…Virtual planning represents an important tool to correct facial asymmetries, allowing greater accuracy in the treatment of these patients, both from the orthodontic and surgical perspectives 11 . Some authors affirm that computerized planning increases the effectiveness of orthognathic surgery, providing more precise osteotomies than with classic planning 12 .…”
Section: Introductionmentioning
confidence: 99%
“…If the patient has a biplanar occlusal plane of the upper jaw, it is important to maintain this and prepare the patient segmentally. Segments are typically formed by osteotomy between the Central incisors into segments 17-11 and 21-27 or between the lateral incisors and canines, whereby the dental arch is divided into three segments second molar to canine, incisors, canine to second molar [26][27][28].…”
Section: Years Old Man With Hfm (Planned Reconstruction Of Joints Str...mentioning
confidence: 99%